2011
DOI: 10.1111/j.1365-2125.2011.03956.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of Entero‐Test, a simple approach for non‐invasive clinical evaluation of the biliary disposition of drugs

Abstract: WHAT IS ALREADY KNOWN ABOUT THE SUBJECT• Biliary secretion is often a major route of elimination of drugs and metabolites. Knowledge of the biliary disposition of a drug in man is important in understanding the contribution of this route to overall clearance and the potential for drug-drug interactions which may have clinical consequences. • Current methods for collecting human bile as part of drug disposition studies are invasive and complex, requiring intubation of the duodenum. As a result, limited data exi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 18 publications
2
27
0
Order By: Relevance
“…Owing to the considerable investment and enabling studies required to support a human radiolabel study [19,20], these studies are often conducted too late in clinical development to impact on the co-medication strategy. Also bile is typically not collected in these studies thereby missing a potential key route of drug elimination [7]. Biliary elimination can sometimes be inferred by the drug-related material in faeces.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to the considerable investment and enabling studies required to support a human radiolabel study [19,20], these studies are often conducted too late in clinical development to impact on the co-medication strategy. Also bile is typically not collected in these studies thereby missing a potential key route of drug elimination [7]. Biliary elimination can sometimes be inferred by the drug-related material in faeces.…”
Section: Discussionmentioning
confidence: 99%
“…A simple method for the collection of duodenal bile in human subjects has been previously reported by Guiney et al [7] and has demonstrated that the Entero-Test®, a commercially available device, could be used reliably to collect human duodenal bile in order to determine metabolites of the lipid lowering drug simvastatin. The work described herein demonstrates a further application of the Entero-Test® technique to aid the assessment of victim drug interaction risk by characterization of the biliary disposition of GSK1325756.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, GSK pioneered its use in metabolism studies. The device has proven useful in sampling bile from both dogs and human subjects in nonradiolabeled metabolism studies (Guiney et al, 2011;Bloomer et al, 2012), but it has never been tested in a conventional human radiolabel study where its application could be fully evaluated.…”
Section: Gsk1322322 (N-((r)-2-(cyclopentylmethyl)-3-(2-(5-fluoro-6-((mentioning
confidence: 99%
“…It is also possible to get qualitative information into metabolic pathways of orally administered drugs in bile with the use of recent techniques such as Entero-Test (Guiney et al, 2011;Bloomer et al, 2013), although this has not yet been widely adopted. Identification of human-specific metabolic pathways along with any saturable pathways (as indicated by nonlinear PK) guides further refinement of victim DDI potential at FIH stage.…”
Section: New Molecular Entities As Victims Of Metabolic Drug-drug Intmentioning
confidence: 99%
“…Recent advances in clinical devices as Entero-Test (Guiney et al, 2011;Bloomer et al, 2013) have enabled direct assessment of drugs and metabolites excreted into the bile of humans. This method can be applied in early clinical development to provide qualitative information on the risk of interactions for drugs that are metabolized and eliminated in bile.…”
Section: Learning From First-in-human Studiesmentioning
confidence: 99%